Risk Factors for Chronic Complications in Type 2 Diabetes Mellitus Patients in Makassar City: A Case-Control Study - Andi Selvi Yusnitasari; Ridwan Amiruddin; Andi Nur Afifah Wahyuni; Andi Tis'a Ramadhani; Ghea Fricillia Sambe (Universitas Mandala Waluya, 2025)
The prevalence of type 2 diabetes mellitus continues to increase globally and has become a significant economic burden on health, making the identification of risk factors for chronic complications important in order to prevent long-term effects. This study aims to analyze risk factors for chronic complications in patients with type 2 DM at five community health centers in Makassar: Sudiang, Ballaparang, Kassi-kassi, Antara, and Paccerakkang. The study design used an analytical observational approach with a case-control approach. The total sample consisted of 100 respondents (50 cases and 50 controls) selected using purposive sampling. Data were collected through interviews and medical records, then analyzed univariately and bivariately (Odds Ratio/OR). The results of statistical analysis showed that age (OR = 2.524; 95% CI = 0.723-8.818), blood pressure (OR = 1.379; 95% CI = 0.628–3.029), GDP (OR = 3.802; 95% CI = 1.482–9.750), duration of DM (OR = 18.614; 95% CI = 6.782–51.087), treatment adherence (OR = 2.263; 95% CI = 1.013–5.052), stress (OR = 1.084; 95% CI = 0.494–2.377), and self-care for DM (OR = 2.495; 95% CI = 1.105–5.629). Based on these findings, patients with type 2 DM are advised to monitor their blood sugar levels regularly, improve adherence to therapy, and implement good self-care practices such as diet management, regular physical activity, and periodic health checkups to prevent chronic complications.